Adherence of multi-micronutrient supplementation and hemoglobin level in children from 6 to 36 months of Huanca Huanca district, Peru, 2017 - Andrea Tinoco Ramos (2019)
Objective: of the study was to determine the factors of adherence to supplementation withmultimicronutrients related to the level of hemoglobin in children from 6 to 36 months of age in thedistrict of Huanca Huanca, Huancavelica. Material and methods: the study was quantitative, nonexperimental,correlational and transversal design approach. The sample was not probabilistic ofintentional type, using the inclusion and exclusion criteria, and consisted of 60 children from 6 to 36months of age. The instrument used for the data collection was the adhesion test for multimicronutrientsupplementation from Espichan (2013) and the hemoglobin measurement was performed withHemocue 201. Results found that 53.3% of the mothers had an average adherence. 53.3% of thechildren had normal hemoglobin. In addition, there is no relationship between the general adherenceto multimicronutrient supplementation and the hemoglobin level, with a p-value of 0.385 and a lowcorrelation was found in the factor related to the supplement with a p-value of 0.042. Conclussion:that both variables are not related.